Establishing a circular economy framework in the agro-waste to ethanol-based supply chain in Karnataka, India - Mohanty, Reema; Patil, Balachandra; Srinivasaiah, Dasappa (Frontiers in Sustainability, 2024)
Waste handling is one of the biggest problems across the globe. An additional challenge of mitigating climate change also arises during the burning of fossil fuel. The fossil fuel-based transportation system in India that gives rise to air pollution has a worse impact on people. To overcome these problems, a sustainability assessment framework is introduced in this study. Ethanol, a member of the biofuel family, is one of the cleanest and most sustainable forms of energy sources. The purpose of this research is to develop a sustainability assessment framework to investigate the environmental feasibility of a supply chain system that provides an end-to-end solution and how it would benefit the transportation sector. A second-generation (2G) ethanol-based supply chain is envisaged, and agro-waste such as corncobs and paddy straw are considered in this study. The assessment is carried out using a heuristic-based method, known as particle swarm optimization (PSO) technique, within the framework of circular economy. The results show that the biomass collection in the proposed area produces 2.5 tons of CO2 per hectare area on average, which is much lower in comparison to 996.6 tons of CO2 per hectare in the Middle East, the main source of fossil fuel. In the future, this research would benefit the enterprises and government organizations that establish 2G ethanol plants.